A sharing economy fogalma és a vele kapcsolatos attitűdök vizsgálata Magyarországon - Csapóné Riskó Tünde; Nábrádi Zsófia; Kiss Virág Ágnes (2019)
The term "sharing economy" (collaborative consumption or economy) began to appear in the early 2000s. It is a business model of acquiring, providing or sharing access to goods and services that are facilitated by a community based on-line platform. Through this business model negative environmental impacts can be reduced through decreasing the amount of goods needed to be produced, consumer costs can be lowered by borrowing and recycling items, sustainable consumption and production patterns can be accelerated. The aim of our primary research was to explore the informedness and attitudes of our respondents towards the certain sectors of sharing economy. It has been explored that in case of certain sectors respondents are actively involved or interested in, while in case of some other sectors the possibilities are not utilised or even known. Based on our investigation, the mobility, multimedia and touristic platforms proved to be the most well-known sectors of sharing economy.
Keywords: Társadalomtudományok; Közgazdasági és gazdálkodástudományok